Parameters of intrathyroid hemodynamics in patients with nodular toxic goiter - Zavgorodniy, S. M.; Gatia, M. S.; Kubraк, M. A.; Danyliuk, M. B.; Завгородній, Сергій Миколайович; Гатіа, Мохаммед Саддам; Кубрак, Михайло Анатолійович; Данилюк, Михайло Богданович (My University, 2023)
Introduction. One of the main places in the structure of thyrotoxicosis in Ukraine and the world is occupied by nodular toxic goiter. The purpose of the study. To analyze the results of intrathyroid hemodynamics in the modes of color and energy Doppler mapping and pulse Doppler in patients with nodular toxic goiter. Research object and methods. The research was conducted on the basis of the «VIZUS» medical center, where 35 (100%) patients with toxic goiter were examined and subsequently operated on. All 35 (100%) patients had intrathyroid hemodynamic parameters determined in the modes of color and energy Doppler mapping and pulsed Doppler. Research results and their discussion. In patients with nodular toxic goiter, 2 and 3 types of vascularization according to the scale of Rago T. prevailed (32 (91.4%) patients) and normal or small increase in the intensity of blood flow in the thyroid parenchyma (15 (75.0%) patients). In 29 (82.9%) patients, an increase in the peak systolic blood flow velocity in the vasculature was found (34.2 (19.4; 41.2) cm/s), in 24 (68.6%) there was an increase in the maximum diastolic blood flow velocity (16.2 (9.8; 20.8) cm/s), the maximum volumetric velocity of blood flow was increased in 27 (77.1%) examined (1.4 (0.8; 1.6) ml/s), the resistance index was increased in 11 (31.4%) patients before 0.9 (0.6; 1.1). Conclusions. 1. According to the results of dopplerography, perinodular and mixed types of vascularization with normal or slightly increased blood flow in the thyroid parenchyma were found in most cases in patients with toxic nodular goiter. 2. In patients with nodular formations in one part of the thyroid gland, no significant difference in the intensity of intrathyroidal blood flow was found in the affected and contralateral (healthy) parts of the gland, U=345.0; p=0.6713. 3. No significant changes in the quantitative parameters of the blood flow of the affected and healthy lobes of the thyroid gland were found in patients with hyperthyroidism when one of the lobes of the thyroid gland was damaged. Вступ. Одне з основних місць в структурі тиреотоксикозу в Україні та світі займає вузловий ток- сичний зоб (ВТЗ). Мета дослідження. Провести аналіз результатів дослідження інтратиреоїдної гемодина- міки в режимах кольорового та енергетичного доплерівського картування та імпульсної доплерографії у па- цієнтів з вузловим токсичним зобом. Об’єкт і методи дослідження. Дослідження було проведено на базі медичного центру «ВІЗУС», де було обстежено та в подальшому прооперовано 35 (100%) пацієнтів з ВТЗ. Всім 35 (100,0%) пацієнтам проведено визначення показників інтратиреоїдної гемодинаміки в режимах кольоро- вого та енергетичного доплерівського картування та імпульсної доплерографії. Результати дослідження та їх обговорення. У хворих з вузловим токсичним зобом переважали 2 та 3 типи васкуляризації згідно шкали Rago Т. (32 (91,4%) пацієнтів) та нормальне або мале посилення інтенсив- ності кровотоку тиреоїдної паренхіми (15 (75,0%) хворих). У 29 (82,9%) хворих виявлено підвищення пікової систолічної швидкості кровотоку в ВЩА (34,2 (19,4; 41,2) см/с), у 24 (68,6%) було підвищення максимальної діастолічної швидкості кровотоку (16,2 (9,8; 20,8) см/с), максимальна об’ємна швидкість кровотоку була під- вищена у 27 (77,1%) обстежених (1,4 (0,8; 1,6) мл/с), індекс резистентності був збільшений у 11 (31,4%) хворих до 0,9 (0,6; 1,1). Висновки. 1. У хворих з ВТЗ, за результатами доплерографічного дослідження, у більшості випадків виявлено пери- нодулярний та змішаний типи васкуляризації з нормальним або мало посиленим кровотоком в тиреоїдній паренхімі. 2. У пацієнтів з вузловими утвореннями в одній частці ЩЗ не виявлено достовірної різниці в інтенсивності інтратиреоїдного кровотоку в ураженій та контрлатеральній (здоровій) частках залози, U=345,0; p=0,6713. 3. У пацієнтів з ВТЗ при ураженні однієї з часток ЩЗ не виявлено достовірних змін в кількісних параметрах кровотоку ураженої та здорової часток щитоподібної залози.
Параметри інтратиреоїдної гемодинаміки у пацієнтів з вузловим токсичним зобом
Zavgorodniy S. M. - 0000-0003-3082-3406; Gatia M. S. - 0000-0003-4061-6478; Kubrak M. A. - 0000-0003-4051-9336; Danyliuk M. B. - 0000-0003-4515-7522.
Keywords: nodular toxic goiter; hemodynamics; intrathyroidal blood flow; dopplerography; вузловий токсичний зоб; гемодинаміка; інтратиреоїдний кровотік; доплерографія